2021
DOI: 10.1002/14651858.cd008350.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatic retinopexy versus scleral buckle for repairing simple rhegmatogenous retinal detachments

Abstract: Pneumatic retinopexy versus scleral buckle for repairing simple rhegmatogenous retinal detachments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
0
10
0
2
Order By: Relevance
“…Thus, the authors of a Cochrane review (Znaor L. et al, 2019) [15] based on an analysis of 10 studies in European countries, India, Iran, Japan and Mexico, which included 1307 patients, concluded that PPV compared to SB less often leads to repeated RD, with the exception of iatrogenic and cataract progression cases, but has the same result in terms of visual recovery. The authors of another Cochrane review (Sena D.F. et al, 2021) [16] based on the analysis of the results of studies conducted in Ireland, the USA and Italy, which included 274 participants (276 eyes), concluded that SB can be more or less equally effective compared to pneumatic retinopexy (PR) in terms of reliability of chorioretinal adhesion and reduction of the risk of re-detachment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the authors of a Cochrane review (Znaor L. et al, 2019) [15] based on an analysis of 10 studies in European countries, India, Iran, Japan and Mexico, which included 1307 patients, concluded that PPV compared to SB less often leads to repeated RD, with the exception of iatrogenic and cataract progression cases, but has the same result in terms of visual recovery. The authors of another Cochrane review (Sena D.F. et al, 2021) [16] based on the analysis of the results of studies conducted in Ireland, the USA and Italy, which included 274 participants (276 eyes), concluded that SB can be more or less equally effective compared to pneumatic retinopexy (PR) in terms of reliability of chorioretinal adhesion and reduction of the risk of re-detachment.…”
Section: Resultsmentioning
confidence: 99%
“…The authors of another Cochrane review (Sena D.F. et al, 2021) [16] based on the analysis of the results of studies conducted in Ireland, the USA and Italy, which included 274 participants (276 eyes), concluded that SB can be more or less equally effective compared to pneumatic retinopexy (PR) in terms of reliability of chorioretinal adhesion and reduction of the risk of re-detachment. However, the use of SB resulted in more myopic progression, which was interpreted as a sign of cataract development.…”
Section: Resultsmentioning
confidence: 99%
“…Кожний з цих методів має свої переваги та недоліки, межі відновлення гостроти та полів зору, ризики повторних відшарувань та ускладнень [6; 7]. Тривала дискусія про найкращий метод офтальмохірургічного лікування включає обговорення трьох основних методів фіксації шарів сітківки після її відшарування -кріо-, лазеро-та електропексію [7][8][9][10][11][12][13]. Нами було проведено власне експериментальне дослідження відновлення анатомічної цілісності сітківки за допомогою високочастотної електрокоагуляції (сила струму 0,1 А, напруга 10-16 В, частота 66 кГц) супрахоріоїдальним доступом, інструментом оригінальної конструкції з діаметром кінцевої сфери 25 G [14; 15].…”
Section: вступunclassified
“… 101 A recent Cochrane review concluded that PR had a lower reattachment rate and a higher recurrence rate but a lower burden of post-operative complications compared to SB. 102 Data from a commercial insurance database from the USA showed that almost 30% of cases managed by primary PR compared to 20% of cases managed by either SB or PPV required a reoperation within 90 days of the primary repair. 103 More recently, the Primary Retinal Detachment Outcomes 104 Study reported that in phakic patients there was, not only a higher success rate with a single procedure with SB compared to patients undergoing PPV (91.7% vs 83.1%) but also a better visual acuity in patients undergoing SB.…”
Section: Outcomes Of Retinal Re-attachment Proceduresmentioning
confidence: 99%